Tingkat pengetahuan siswa tentang permainan bulu tangkis kelas VIII di SMP Negeri 1 Purwasari Kabupaten Karawang - Rizkyandra, Dwiky Rama; Nasution, Nana Suryana; Achmad, Irfan Zinat (Jurnal Porkes, 2024)
The problem of this research is the need to increase the knowledge of students who do not know about the rules of the game. The purpose of this study was to assess the level of student knowledge about badminton games. This study used a quantitative approach and survey method. The population amounted to 372 students, the technique of taking simple random sampling. The instrument used was a questionnaire. Data analysis carried out quantitative descriptive includes total value, range, average, standard deviation, minimum value and maximum value.  Based on the data obtained, it can be seen that the level of students' knowledge of badminton games in the “very good” category is 2.56% (5 students), the “good” category is 63.08% (123 students), the “sufficient” category is 21.54% (42 students), the “less” category is 3.59% (7 students), the “very less” category is 9.23% (18 students), thus obtaining an average value of 16.44% from a total of 20 questions. So it can be concluded that the overall level of student knowledge about badminton games is in the moderate category.